2022
DOI: 10.1111/jce.15472
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for repeat procedures in patients with persistent atrial fibrillation: Systematic linear ablation with adjunctive ethanol infusion into the vein of Marshall versus electrophysiology‐guided ablation

Abstract: Introduction The optimal strategy after a failed ablation for persistent atrial fibrillation (perAF) is unknown. This study evaluated the value of an anatomically guided strategy using a systematic set of linear lesions with adjunctive ethanol infusion into the vein of Marshall (Et‐VOM) in patients referred for second perAF ablation procedures. Methods and Results Patients with perAF who underwent a second procedure were grouped according to the two strategies. The first strategy was an anatomically guided app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In fact, an incomplete block of the linear lines created with RFA or reconduction in the created lines after RFA may be strongly associated with postoperative AT/AF recurrences. Regarding the durability of the linear lines created with RFA in patients with AF/AT recurrences, some previous studies have shown the recurrence rate to be over 30% for both LA roof 6,16 and MI 13 lines, exposing the difficulty of creating transmural lesions in the MI or LA roof only with RFA.…”
Section: An Extensive Af Ablation Strategy With Cba Rfa and Ea-vommentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an incomplete block of the linear lines created with RFA or reconduction in the created lines after RFA may be strongly associated with postoperative AT/AF recurrences. Regarding the durability of the linear lines created with RFA in patients with AF/AT recurrences, some previous studies have shown the recurrence rate to be over 30% for both LA roof 6,16 and MI 13 lines, exposing the difficulty of creating transmural lesions in the MI or LA roof only with RFA.…”
Section: An Extensive Af Ablation Strategy With Cba Rfa and Ea-vommentioning
confidence: 99%
“…[4][5][6][7] Further, recent studies have also shown improved outcomes from the novel strategy of adding ethanol ablation to the vein of Marshall (EA-VOM). [8][9][10][11][12][13] However, those previous studies separately demonstrated the effectiveness of each ablation strategy including cryoballoon ablation (CBA), [4][5][6][7] EA-VOM, [8][9][10][11][12][13] or other ablation strategies with RFA. The present study aims to investigate the safety and efficacy of a novel extensive ablation strategy that combines CBA, RFA, and EA-VOM in de novo AF ablation for non-paroxysmal AF.…”
Section: Introductionmentioning
confidence: 99%
“…In EARNEST-PVI trial, 85% of patients underwent additional linear ablation and did not have a significantly better outcome than the PVI only group at 12 months (30). When performing mitral isthmus ablation, the use of adjunctive VOM ethanol infusion has been shown to be associated with a higher rate of mitral isthmus block and arrhythmia free survival mainly driven by a lower AT recurrence (31)(32)(33).…”
Section: Linear Lesionsmentioning
confidence: 99%
“…A significantly higher freedom rate from AF or prolonged atrial tachycardia (49% vs. 38% at both 6 and 12 months) was observed in patients who received catheter ablation with VOM ethanol infusion [ 40 ]. In patients with PeAF who underwent a second procedure, the strategy using systematic linear ablation with VOM ethanol infusion had lower recurrence when compared with the strategy using atrial tachyarrhythmia termination as the procedural endpoint [ 41 ]. A recent meta-analysis including 1337 patients compared the long-term outcomes between catheter ablation with VOM ethanol infusion and ablation alone [ 42 ].…”
Section: The Role Of Vom Ethanol Infusion In Peaf Ablationmentioning
confidence: 99%